Comparison of production of bioactive components in Zanthoxylum nitidum taproots from different regions in southern China. (18th March 2023) - Yang, Yang; Li, Yanqun; Amoroso, Victor; Acma, Florfe; Guiang, Maria Melanie; Wu, Hong
Abstract: Zanthoxylum nitidum (Roxb.) DC is a traditional Chinese herb from southern China and its 3–4‐year old roots are used in medicine. However, there is a scarcity of studies on the differences in the content of different regions of the roots, as well as comprehensive evaluations of Z. nitidum from the main areas of production in China. This study used ultra performance liquid chromatography, triple quadrupole tandem mass spectrometry, HPLC, and Fourier‐transform infrared spectroscopy to detect and identify the bioactive components from different parts and eight regions of 4‐year‐old roots of Z. nitidum . Our results revealed that the types and quantities of compounds extracted were similar in root bark and root wood, although the amount of alkaloids in the former was substantially higher. The contents of four alkaloids in samples from Guangdong were higher than those in Guangxi Province. Meanwhile, hierarchical cluster analysis and principal component analysis showed that the samples from different regions were effectively identified and evaluated based on alkaloids and other bioactive substances. Our findings have significant implications for Z. nitidum harvesting and usage, as well as for origin identification, quality evaluation, and sensible use of Z. nitidum resources.